GLIAL FIBRILLARY ACIDIC PROTEIN SEBAGAI PREDIKTOR KEMATIAN CIDERA KEPALA - , Wahid Syamsul Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The incidence of head injury due to trauma increases the morbidity and mortality is relatively high, thus requiring a fast and precise handling to get a good clinical output. Handling head injury is determined by the diagnosis and prognosis that will happen. Investigations are often performed is the Computed Tomography scan (CT scan) and Magnetic Resonance Imaging (MRI), both of which can only be done in hospitals that have such facilities, the examination requires the mobilization of the patient, and is relatively expensive. Therefore, the proposed inspection GFAP (Glial Fibrillary Acidic Protein) to assess the prognosis of head injury. This study aims to assess the role of serum GFAP as a predictor of head injury deaths. This was an analytic observational prospective cohort study by counting the RR increased glial Fibrillary Acid Protein (GFAP) to death in head injury. To assess the increase in GFAP in serum (s-GFAP) after head injury, we collected serum samples from 80 patients with severe head injury begins on the day of trauma. S-GFAP was measured using ELISA Reader. GCS assessed to see the outcome of the output.